Self-help online psychoeducation to overcome anxiety during covid-19 outbreak. - Suranata, Kadek; Ifdil, Ifdil; Gading, I Ketut; Permana, Agus Aan Jiwa (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
This study aims to compare the effectiveness of mindfulness and relaxation techniques with self-help methods through web tutorials to overcome anxiety during the Covid-19 outbreak. Random control trial experiment performed by invite 418 Balinese Community (Age 15 years and above) to preliminary screening on anxiety sub-scale of 21-DASS. A total of 129 participants who met the random assignment criteria were then grouped into three groups, namely experimental group 1 who will take self-help mindfulness exercises, experimental group 2 who will participate in self-help relaxation exercises, and waiting-list control group. The results of study shows that web-based self-help mindfulness and relaxation tutorials are effective for reducing anxiety levels. The comparison of the two also shows that mindfulness techniques are more effective than relaxation techniques. The results of this study have theoretical and practical implications in efforts to overcome anxiety disorders experienced during the Covid-19 outbreak.